2013
DOI: 10.1111/ejn.12257
|View full text |Cite
|
Sign up to set email alerts
|

Signaling mechanism underlying α2A‐adrenergic suppression of excitatory synaptic transmission in the medial prefrontal cortex of rats

Abstract: Stimulation of α2A‐adrenoceptors (ARs) in the prefrontal cortex (PFC) produces a beneficial effect on cognitive functions such as working memory. A previous study in our laboratory showed that α2A‐AR stimulation suppresses excitatory synaptic transmission in layer V‐VI pyramidal cells of the rat medial PFC (mPFC). However, the intracellular mechanism underlying the α2A‐AR suppression remains unclear. In the present study, we recorded evoked excitatory postsynaptic current (eEPSC) in layer V‐VI pyramidal cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 40 publications
0
28
1
2
Order By: Relevance
“…Yi and colleagues have shown that the α 2A receptor agonist, guanfacine, significantly suppressed evoked AMPA-EPSCs in PFC pyramidal cells. Overall, the a 2A receptor inhibition is mediated by the G i -cAMP-PKA-PP1-calcium/calmodulin-dependent protein kinase II (CaMKII)-AMPA receptor signaling pathway that can be blocked by different kinase antagonists at different levels (Yi et al, 2013). Conversely, under specific situations such as emotional arousal, NE recruits β receptors to activate the AC-cAMP-PKA-CaMKII pathway, leading to phosphorylation of GluR1 at sites critical for synaptic delivery of AMPARs and memory enhancement (Hu et al, 2007; Tenorio et al, 2010).…”
Section: Ne and Da Modulation Of Synaptic Transmission In The Pfc mentioning
confidence: 99%
“…Yi and colleagues have shown that the α 2A receptor agonist, guanfacine, significantly suppressed evoked AMPA-EPSCs in PFC pyramidal cells. Overall, the a 2A receptor inhibition is mediated by the G i -cAMP-PKA-PP1-calcium/calmodulin-dependent protein kinase II (CaMKII)-AMPA receptor signaling pathway that can be blocked by different kinase antagonists at different levels (Yi et al, 2013). Conversely, under specific situations such as emotional arousal, NE recruits β receptors to activate the AC-cAMP-PKA-CaMKII pathway, leading to phosphorylation of GluR1 at sites critical for synaptic delivery of AMPARs and memory enhancement (Hu et al, 2007; Tenorio et al, 2010).…”
Section: Ne and Da Modulation Of Synaptic Transmission In The Pfc mentioning
confidence: 99%
“…Guanfacine is suggested to exert its positive effects on cognitive functions via these actions on post-synaptic a2A-NAR receptors in the dorsolateral PFC5. Guanfacine is also suggested to suppress glutamatergic synaptic transmission and thereby neural excitability at deeper layers (V/VI) in PFC, potentially governed by similar intra-cellular mechanisms as those controlling HCN channels2122. It has been proposed that at low concentrations, Guanfacine’s actions on HCN channels may predominate, while only at high concentrations glutamate transmission is affected, potentially explaining an inverted-U type function of Guanfacine522.…”
mentioning
confidence: 99%
“…Guanfacine is also suggested to suppress glutamatergic synaptic transmission and thereby neural excitability at deeper layers (V/VI) in PFC, potentially governed by similar intra-cellular mechanisms as those controlling HCN channels2122. It has been proposed that at low concentrations, Guanfacine’s actions on HCN channels may predominate, while only at high concentrations glutamate transmission is affected, potentially explaining an inverted-U type function of Guanfacine522. Guanfacine also binds to pre-synaptic alpha 2A receptors on locus coeruleus terminals that act as inhibitory auto-receptors, thereby decreasing NE release23, which may again suggest that high doses of Guanfacine could impair cognitive functions.…”
mentioning
confidence: 99%
“…In vitro recordings from layer II/III pyramidal cells in PFC slices found results similar to monkeys, in which α2A-AR stimulation enhances persistent firing via HCN channel closure (81); however, recordings of layer V neurons show reduced presynaptic glutamate release (82, 83), again emphasizing the differences between PFC lamina. Studies in genetically altered mice found that a functional α2A-AR was needed for guanfacine to produce cognitive improvement (84).…”
Section: The α2a-adrenoceptor Agonist Guanfacine Improves Prefrontal mentioning
confidence: 71%